A Clinical Perspective of Anti-Fibrotic Therapies for Cardiovascular Disease - Fang, Lu; Murphy, Andrew J.; Dart, Anthony M. (Frontiers in Pharmacology, 2017)
Cardiac fibrosis are central to various cardiovascular diseases. Research on the mechanisms and therapeutic targets for cardiac fibrosis has advanced greatly in recent years. However, while many anti-fibrotic treatments have been studied in animal models and seem promising, translation of experimental findings into human patients has been rather limited. Thus, several potential new treatments which have shown to reduce cardiac fibrosis in animal models have either not been tested in humans or proved to be disappointing in clinical trials. A majority of clinical studies are of small size or have not been maintained for long enough periods. In addition, although some conventional therapies, such as renin-angiotensin-aldosterone system inhibitors, have been shown to reduce cardiac fibrosis in humans, cardiac fibrosis persists in patients with heart failure even when treated with these conventional therapies, indicate a need to develop novel effective anti-fibrotic therapies in cardiovascular disease. In this review article, we summarize anti-fibrotic therapies for cardiovascular disease in humans, discuss the limitations of currently used therapies, along with possible reasons for the failure of so many anti-fibrotic drugs at the clinical level. We will then explore the future directions of anti-fibrotic therapies on cardiovascular disease, this will include emerging anti-fibrotics that show promise, such as relaxin. A better understanding of the differences between animal models and human pathology, and improved insight into carefully designed trials on appropriate end-points and appropriate dosing need to be considered to identify more effective anti-fibrotics for treating cardiovascular fibrosis in human patients.